IMPLEMENTASI KEGIATAN KUNJUNGAN RUMAH OLEH GURU BK DALAM MENYELESAIKAN MASALAH PESERTA DIDIK - Derwina, Ririn - (Bimbingan dan Konseling, 2014)
This research was have background from activity of visited home that done by counselordid not carried out with well, until problem solving of the students are not yet maximal. Thisresearch is a qualitative research that produces descriptive. The key informants in this research are3 counselors. Additional informants in this research are 8 students who have been ever visited theirhome by counselor. The instruments used in this research are interviews and documentationstudies. The data analyses are data reduction, data presentation and conclusion. The results showthat 1) the form of home visit establishes planning that the students should be do, but do not askpermission to the students before doing home visit 2) the implementation of meeting to discuss ofstudents problem until get the conclusion and make a family commitment in solving problem ofthe students 3) the form of evaluation by doing of observation, can home visit walk well 4) theform of analysis result evaluation by looking of absent and information from teacher of learners 5)the form of follow-up of continue by home visit and carry out of individual counseling service andinformation service about the rules of school and increase the self-motivation.